Efektifitas Metode Nadir Compromise Programming dalam Menentukan Nilai Optimum Portofolio Saham - Wandi Noviyanto; Ni Ketut Tari Tastrawati; Kartika Sari (Jurnal Matematika, 2016)
Nadir Compromise Programming (NCP) is one of method that can be used to solve multiobjective problem using certain parameter. One of the problem that can be solved by these method is to get the optimum value of stock portfolio. The purpose of this study was to determine on what value of parameter among six values of parameter, NCP models effective in determining the optimum value of the stock portfolio. The data used in this research was secondary data in the form of daily data from the price of 6 types of stocks from October 2013 to October 2015. In this study, the optimum value of the stock portfolio was calculated by the the NCP model at 6 parameter values, i.e. 1, 10, 100 , 1000, 10000, and 100000. As a result of this study showed that the NCP model effective in determining the optimum value of the stock portfolio on parameter 1.